LIMITES À APLICABILIDADE DAS CONVENÇÕES DE VARSÓVIA E MONTREAL NA RESPONSABILIZAÇÃO CIVIL POR DANOS EM VOOS INTERNACIONAIS - BEZERRA, GUTEMBERG ANGELO (2021)
This monograph addresses the limits of applicability of the Warsaw and Montreal conventions on civil liability for damage caused on international flights. It seeks to answer the following problem: do these conventions apply to any and all damages suffered by the consumer on an international flight? It aims, therefore, to delimit the points of application of these conventions in civil liability for damages suffered by consumers on international flights. It presents the theory of dialogue of sources for better construction of consumer protection and defense and its relationship with civil liability for the fact of service in international air transport. Use up the qualitative scientific method, based on descriptive analysis and using the deductive approach, drawing on the analysis of legislation, doctrine, scientific articles, jurisprudence and judgments. Analyze civil liability in the Consumer Defense Code, in the federal constitution and in the Civil Code, exposing the importance of the quality and safety of products and services, civil liability for the fact of the product and service and civil liability for the fact of the transport service. Furthermore, in the specificity of the theme, approached the issue of limiting the applicability of civil liability for damages caused on international flights, discusses the model established in the Warsaw and Montreal Conventions and its conflict with the consumer protection code, critical analysis of the paradigm established by the Federal Supreme Court (STF). Points out the jurisprudential understanding adopted by the Brazilian courts considering the years 1977 to 2017. Demonstrates its relevance through the critical analysis of the paradigm shift incorporated by the STF into the Brazilian legal understanding by establishing the prevalence of the Warsaw and Montreal Conventions on the Defense Code of the Consumer only regarding to material damages and not to moral damages. Finally, it concluded that the Warsaw and Montreal convetions are limited only to material damages, with the CDC being established to cover moral damages.